2021
DOI: 10.1007/s11606-020-06506-6
|View full text |Cite
|
Sign up to set email alerts
|

Development and Pilot Testing of a Patient-Centered Web-Based Reproductive Decision Support Tool for Primary Care

Abstract: BACKGROUND: Patient-centered counseling to help women achieve their reproductive goals is an essential yet often absent component of primary care. OBJECTIVE: We developed and piloted MyPath, a novel web-based decision support tool integrating reproductive goals assessment, information about optimizing health before pregnancy, and contraceptive decision support, for use prior to primary care visits in the Veterans Administration (VA). DESIGN: We created MyPath using best practices for decision tool development,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 62 publications
0
55
0
Order By: Relevance
“…In a nonrandomized pilot of the final prototype (control group, n=28; intervention group, n=30), we found that a greater proportion of intervention participants reported having discussions about their reproductive needs in the visit compared to controls (93% vs 68%; P=.02) [34]. A multisite hybrid effectiveness-implementation randomized controlled trial is currently ongoing to evaluate the impact of the text message-delivered MyPath on various person-centered and clinical outcomes, with the goal of ultimately scaling the intervention nationally within VA if found to be effective.…”
Section: Reproductive Care For Nonpregnant People With Mypathmentioning
confidence: 90%
See 1 more Smart Citation
“…In a nonrandomized pilot of the final prototype (control group, n=28; intervention group, n=30), we found that a greater proportion of intervention participants reported having discussions about their reproductive needs in the visit compared to controls (93% vs 68%; P=.02) [34]. A multisite hybrid effectiveness-implementation randomized controlled trial is currently ongoing to evaluate the impact of the text message-delivered MyPath on various person-centered and clinical outcomes, with the goal of ultimately scaling the intervention nationally within VA if found to be effective.…”
Section: Reproductive Care For Nonpregnant People With Mypathmentioning
confidence: 90%
“…Veterans capable of pregnancy who use VA Health Care services are a highly diverse population, with nearly half identifying as racial or ethnic minoritized groups [32], and face elevated risks of adverse pregnancy and birth outcomes compared to their civilian counterparts due to a higher prevalence of medical, mental health, and psychosocial factors [33]. Drawing on our first principle (Principle 1: Interdisciplinary stakeholder-inclusive teams), MyPath development was informed by formative qualitative work to understand veterans' preferences and needs [25] and followed user-centered design principles, guided by patient, provider, and scientific expert input [34]. Designed to be used prior to primary care visits, MyPath empowers patients by helping them clarify and share their reproductive goals with their primary care providers, augmenting their knowledge, and building self-efficacy in communicating about their reproductive needs (Principle 2: Facilitating a patient-centered approach).…”
Section: Reproductive Care For Nonpregnant People With Mypathmentioning
confidence: 99%
“…Depending on the woman's responses, Gabby works with them over time to meet her reproductive and general health goals. Building on the PATH tool, 25 26 the online MyPath reproductive goals assessment 32 was designed to be used prior to primary care visits. Tested in women Veterans in the United States, MyPath also included information about reproductive health and contraception.…”
Section: Discussionmentioning
confidence: 99%
“…Another consideration is the use of patient-facing reproductive decision-support tools that can be deployed ahead of an appointment to educate and identify issues to address in a comprehensive primary care visit. 27…”
Section: Veteran Levelmentioning
confidence: 99%